Reducing central line-associated bloodstream infections (CLABSI) by improved identification of primary infection sites through preliminary blood culture notifications - Werner E. Bischoff; Cheryl Kieta; Tiffany LaFontaine; Corrianne Billings (Cambridge University Press, 2024)
Central line-associated bloodstream infections (CLABSI) pose a significant patient risk. To address incorrect classifications of infectious events as CLABSI, the surveillance process was changed from using finalized blood culture to preliminary blood culture results as trigger of timely, in-depth reviews. This improved the detection of true CLABSI events.